KEBEBASAN BEREKSPRESI DI ERA MEME: DINAMIKA BUDAYA, KREATIVITAS, DAN ETIKA DIGITAL - Absari, Chairullia (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
The development of digital culture has given rise to memes as a form of popular expression used by society, especially among young people, to convey social and political criticism. Memes offer quick, visual, and meaningful message delivery, but also present ethical and legal challenges. This study aims to analyze the function of memes in the practice of freedom of expression and to examine the boundaries between creativity, social norms, and digital regulations. The method used is a qualitative approach through literature study. Data sources were obtained from scientific journals, online news, academic books, and relevant legal documents. Thematic descriptive analysis was conducted to identify the role of memes as a tool for criticism and the dynamics of the challenges involved. The findings show that memes can serve as a participatory medium in shaping public opinion and voicing criticism on socio-political issues. However, challenges such as loss of context, opinion polarization, and the risk of criminalization under the Electronic Information and Transactions Law (UU ITE) remain significant obstacles. Therefore, improving digital literacy and adopting adaptive policy approaches are necessary to ensure that expression through memes remains within ethical and democratic boundaries.